A computational fluid dynamics study pre- and post-fistula closure in a coronary artery fistula. Issue 1 (2nd January 2020) - Cao, Haoyao; Qiu, Yue; Yuan, Ding; Yu, Jianqun; Li, Da; Jiang, Yi; Su, Li; Peng, Liqing; Zheng, Tinghui
Abstract: This study numerically investigated the hemodynamics of a patient-specific coronary artery fistula (CAF) before and after the fistula closure. The results indicated that the dilated fistula result in inadequate perfusion to other healthy aortas. Disturbed blood flow, aberrant WSSs, local negative pressure gradients and sharp pressure changes are shown in both untreated and occluded fistula. Furthermore, extreme high WSS appeared at the fistula bending after the terminal closure. It was concluded that the fistula closure may effectively improve the phenomenon of stealing blood but worsen the unfavorable hemodyanmics predisposing the thrombosis formation due to its geometrical torturosity.